High Blood Pressure Combined with Sedentary Behavior in Young People: A Systematic Review - Sanches Silveira, Loreana; Sayuri Inoue, Daniela; Messias Rodrigues da Silva, Jose; Ungari Cayres, Suziane; Giulliano Destro Christofaro, Diego (Current Hypertension Reviews, 2016)
Background: High blood pressure (HBP) is a cardiovascular risk factor that can initiate in childhood and adolescence and may be associated with other risk factors such as sedentary lifestyles. Therefore, verifying if these associations occur from the earliest ages is of fundamental importance. Objectives: to report the prevalence of HBP combined with sedentary behavior through a systematic review. Design and Methods: The research was performed based on studies published between 2010 and 2016 in Medline, Web of Science, Excerpta Medica (EMBASE), and Scielo, using terms related to: ‘sedentary behavior’ OR ‘screen time’ AND ‘high blood pressure’. In the initial search, 821 studies were found and after exclusions twelve studies were included in the review. Results: Twelve studies addressing the relationship between sedentary behavior and HBP were found. Eighty-three percent of the studies evaluated sedentary behavior using a questionnaire (n = 10). The majority of studies analyzed in the review were conducted in North America (41.6%). Only four studies presented the prevalence of HBP related to sedentary behavior (variation 1-22.9%). In seven studies a close relationship between sedentary behavior and HBP was observed. Conclusions: Although most studies observed a relationship between sedentary behavior and HBP, the results still need to be further explained. Based on the findings of this review, follow-up studies and objective measurements of time spent in sedentary behavior in young people could help to determine the cause-effect relationship between sedentary behavior and HBP in pediatric populations.
Keywords: Sedentary behavior